Correction: In situ study of strontium segregation in La0.6Sr0.4Co0.2Fe0.8O3- δin ambient atmospheres using high-temperature environmental scanning electron microscopy (J. Mater. Chem. A (2018) DOI: 10.1039/c8ta01341a) - Niania,M; Podor,R; Britton,TB; Li,C; Cooper,SJ; Svetkov,N; Skinner,S; Kilner,J (Journal of Materials Chemistry A, 2018)
© 2018 The Royal Society of Chemistry. Correction for 'In situ study of strontium segregation in La0.6Sr0.4Co0.2Fe0.8O3-δin ambient atmospheres using high-temperature environmental scanning electron microscopy' by Mathew Niania et al., J. Mater. Chem. A, 2018, DOI: 10.1039/c8ta01341a. The authors regret that the name of the first author of ref. 37 was displayed as "F. Pisigkin". The correct name should be "F. Piskin". The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers.